PROTOTIPE ROBOT PEMBERSIH LANTAI BERBASIS MIKROKONTROLER - tamam, muhammad taufiq (Universitas Lampung, 2023)
The development of automation has penetrated into all areas of life, including household appliances. One of them is robot technology for cleaning floors. With relatively small dimensions, this floor cleaning robot can reach under a table or bed. This floor cleaning robot is equipped with a microcontroller, suction pump and ultrasonic sensor to detect obstacles when scanning the floor surface. The microcontroller will process the ultrasonic sensor readings. If an obstacle is detected, the robot will avoid it by turning right or left. The suction pump is made of a 12 V DC motor with a suction power of 0.19 W for dust and 1.09 W for paper scraps. Based on the test results, this robot has a suction speed of 2.14 m/s and a suction capacity of 5.44x10-4 m3/s. With this floor cleaning robot, the job becomes lighter and easier.